Answer:
A' (-3,7)
B' (0,10)
C' (12,10)
D' (-2,-4)
Step-by-step explanation:
A' (-6+3 , 3+4) = (-3,7)
B' (-3+3 , 6+4) = (0,10)
C' (9+3 , 6+4) = (12,10)
D' (-5+3 , -8+4) = (-2,-4)
5000 meter because there is 1000 meters in 1 kilometer
Answer:
A
Step-by-step explanation:
The function has vertical asymptotes at x=7 and x=-3, so the denominator needs to have factors (x-7) and (x+3).
This eliminates all the options except for A.
Given expression:
2x(x + 7)-(3x +1);
To distribute implies to spread a process equally in an expression. Often times, the distributive property is used for expressions inside parentheses;
2x(x + 7)-(3x +1)
Distribute 2x over the first parentheses;
the negative sign distributes over the second part
= (2x² + 14x) - 3x -1
= 2x² + 14x -3x -1
Add like terms;
= 2x² + 11x -1
This expression 2x² + 11x -1 is equal to the given one
Answer:
2 and 3
Step-by-step explanation:
6 = 2 × 3, so if a number is divisible by 6, it is also divisible by 2 and 3.